A CRITICAL REVIEW OF ENGLISH ESSAY WRITING IN STUDIES OF CRITICAL THINKING, READING HABITS, AND SENTENCE STRUCTURE MASTERY - Ikhfi Imaniah (Indonesian EFL Journal, 2022)
In academic life, writing skill is the most important part for students because writing skill requires students to be able to think critically and develop the contents of their academic writing. Academic writing skill at University level usually develop Essay writing skill which is focus on analyzing, developing ideas, and opinion in a way that is by providing examples and evidence which can support the essay writing. However, in reality there are still many students unable to develop their main ideas and support their essay writing with evidence and facts. In this study, the samples tested were 64 semester V students using quantitative causality survey methods with path analysis to test each variable. Tests and questionnaires are included in this research. Findings show that essay writing skill simultaneously can be influenced by critical thinking, reading habits and sentence structure mastery. These correlations have implications for the research designs and measures used, and how data were collected. Many studies describe the correlation in global way but none describe the reflection of essay writing rubric on student’s critical thinking. Recommendation for future research is provided.Keywords: Essay writing skills; critical thinking; reading habits; and mastery of sentence structure.